REKONSTRUKSI MODEL SUPERVISI PENDIDIKAN ISLAM BERBASIS PENDEKATAN KLINIS DAN TRANSFORMATIF - Elis Siti Maria Ulfah; Saehu Abas; Nurdi Nuri (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Supervision in Islamic educational institutions has long been practiced in a conventional and bureaucratic manner, focusing primarily on administrative compliance rather than the professional development of educators. This approach frequently fails to address the complex pedagogical realities faced by teachers within Islamic educational contexts. This study aims to reconstruct a supervision model for Islamic education that integrates clinical supervision approaches—which emphasize direct classroom observation, collegial dialogue, and reflective feedback—with transformative supervision approaches that prioritize empowerment, critical consciousness, and systemic change oriented toward Islamic values. Employing a library research methodology, data were drawn from authoritative books and reputable peer-reviewed journals published within the past five years. The findings reveal that a clinical-transformative supervision model grounded in Islamic educational philosophy offers a more holistic, humane, and effective framework for improving teacher professionalism. This reconstructed model positions supervisors not as evaluative inspectors but as partners in professional and spiritual growth within Islamic educational institutions.